Implementasi Program Pembangunan dan Pemberdayaan Masyarakat (Pro-Bebaya) di Kota Samarinda - Fitrah, Muhammad; Budiman; Muhammad Reza Fahlevy (Pencerah, 2024)
This research aims to find out and describe the implementation of Pro-Bebaya program in Gunung Lingai Urban Village in particular in neighbourhood 10 and neighbourhood 22 regions. This research focuses on the forms of activities of Pro-Bebaya which have been targeted in the Mayor's Regulations Number 11 Year 2022 Chapter IV Forms of Activities Article 12 Paragraph 2 namely, procurement, development, then maintenance of public facilities and goods as well as empowerment of the community that covers the fields of infrastructure, economy, social culture, health, education, and youth. Then it also focused on the supportive and inhibitory factors of the implementation of the programme. The authors on this study use a qualitative approach to the type of descriptive research. The data collection technique used is purposive sampling. The results of this study show that the implementation of Pro-Bebaya in the Gunung Lingai area dedicated to neighbourhood 10 and neighbourhood 22 in the first year since the launch of the program has been implemented and in accordance with the mandate of the Pro-bebaya itself. However, there is each one area of the six Pro-Bebaya fields not proposed nor implemented in the area of neighbourhood 10 and neighbourhood 22. For the region of neighbourhood 10, not proposing and not implementing activities in the economic field, while neighbourhood 22 does not propose and do not implement activity in the field of youth, then there are three supporting factors and four inhibiting factors in the implementation of Pro-bebaya in the Gunung Lingai Urban Village of the Penang River district of Samarinda City.